Epstein–Barr virus, the germinal centre and the development of Hodgkin’s lymphoma - Mohamed, G.; Vrzalikova, K.; Cader, F.Z.; Vockerodt, M.; Nagy, E.; Flodr, P.; Yap, L.F.; Diepstra, A.; Kluin, P.M.; Rosati, S.; Murray, P. (Society for General Microbiology, 2014)

(untitled)
The relationship between Epstein-Barr virus (EBV) and the germinal centre (GC) of the asymptomatic host remains an enigma. The occasional appearance of EBV-positive germinal centres in some patients, particularly those with a history of immunosuppression, suggests that EBV numbers in the GC are subject to immune control. The relationship, if any, between lymphoid hyperplasia with EBV-positive germinal centres and subsequent or concurrent lymphomagenesis remains to be clarified. As far as the development of EBV-associated Hodgkin's lymphoma is concerned, the suppression of virus replication, mediated by LMP1 on the one hand, and the loss of B-cell receptor signalling on the other, appears to be an important pathogenic mechanism. A further important emerging concept is that alterations in the microenvironment of the EBV-infected B-cell may be important for lymphomagenesis.